Gastronomical events in the function of promotion of Serbia as tourist destinations - Zrnić, Miloš; Vujić, Milan; Košutić, Jelena; Obradović, Maja; Obradović, Ana (Turističko poslovanje, 2021)
Special attention is paid to gastronomic tourism as a special form of tourism that has become increasingly popular in recent years, which makes countries that are not endowed with natural beauty, favorable climate or rich history, become potentially attractive destinations for visitors. Data collection and analysis focused on food and beverage events in Serbia, shows a tendency to increase the number of the same and indicates the possibility of attracting domestic and foreign guests throughout the year. In addition, the authenticity of the region within Serbia makes their gastronomic offer unique, which contributes to creating a specific experience of increasingly demanding visitors and, consequently, the promotion of Serbia in a competitive tourist market.